2015
DOI: 10.1016/j.bbamem.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naturally occurring arginine 14 deletion on phospholamban conformational dynamics and membrane interactions

Abstract: Phospholamban (PLN) is a single-pass membrane protein that regulates the sarco(endo)plasmic reticulum Ca2+-ATPase (SERCA). Phosphorylation of PLN at Ser16 reverses its inhibitory function under β-adrenergic stimulation, augmenting Ca2+ uptake in the sarcoplasmic reticulum and muscle contractility. PLN exists in two conformations; a T state, where the cytoplasmic domain is helical and absorbed on the membrane surface, and an R state, where the cytoplasmic domain is unfolded and membrane detached. Previous studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Recent progress on solid-state NMR of membrane proteins have demonstrated the importance of using both dipolar- and J-coupling mediated pulse sequences for complete structural mapping 2,28,30,39,57. Phospholamban is a typical example for the application of these methods to demonstrate the change in conformational equilibrium using 1D and 2D experiments 26,27,53,58 . Similar pulse sequences using both 13 C- and 15 N-detected CP- and rINEPT-based experiments have also been applied to various single- and multi-pass membrane proteins including sarcolipin, α-synuclein, bacterial chemotaxis receptor, GPCR, and BamA complex 16,28,5963 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent progress on solid-state NMR of membrane proteins have demonstrated the importance of using both dipolar- and J-coupling mediated pulse sequences for complete structural mapping 2,28,30,39,57. Phospholamban is a typical example for the application of these methods to demonstrate the change in conformational equilibrium using 1D and 2D experiments 26,27,53,58 . Similar pulse sequences using both 13 C- and 15 N-detected CP- and rINEPT-based experiments have also been applied to various single- and multi-pass membrane proteins including sarcolipin, α-synuclein, bacterial chemotaxis receptor, GPCR, and BamA complex 16,28,5963 .…”
Section: Resultsmentioning
confidence: 99%
“…The proposed mechanisms for superinhibition were an imbalance between the pentameric and monomeric PLN forms, resulting in an increase of the monomeric (inhibitory) one [7]. Further studies did not confirm a superinhibitory effect of PLN p.Arg14del in the basal state, but suggested that it might result from an impaired response of mutant PLN to PKA-mediated phosphorylation [8,9]. Although Ca 2+ cycling abnormalities have been detected in cardiac myocytes carrying the mutation [10,11], it remains altogether unclear whether they indeed reflect SERCA2a superinhibition.…”
Section: Introductionmentioning
confidence: 95%
“…The PLN R14del mutation results in a protein that has a stronger affinity for SERCA2a 6 , which has been correlated with the disruption of the Ser 16 phosphorylation motif. It was suggested that disruption of this motif could lead to an increased inhibition of the SERCA2a, cytoplasmic Ca 2+ overload, and increased risk for malignant ventricular arrhythmias 17 , 18 . Whether changes in intracellular Ca 2+ dynamics also occur in vivo and affect cardiac structure and function remains unaddressed.…”
Section: Introductionmentioning
confidence: 99%